PAINÉIS HÍBRIDOS COM MADEIRA DE PINUS REVESTIDOS COM FIBRA DE CARBONO - MUSTEFAGA, ERICK CHAGAS (2022)
The production of wooden panels in Brazil is predominantly carried out with wood from planted forests, mainly from the Pinus and Eucalyptus genera. Currently, research is being carried out with wood panels for the development and characterization of new products, different from those traditionally found on the market and which include the use of wood, in its different forms, in the same product. Therefore, this study was carried out to evaluate the physical and mechanical properties of hybrid panels produced with particles and veneers of Pinus taeda wood in different compositions and reinforced with carbon fiber. Four types of panels were produced in different compositions of blades and particles that were evaluated with and without carbon fiber reinforcement. Urea-formaldehyde resin was used for bonding the particles and blades for manufacturing the hybrid panels, and low viscosity epoxy resin for bonding and impregnating the carbon fiber blanket on the hybrid panel faces. It was verified that the panels produced with the addition of veneers presented greater resistance in the mechanical tests, except for the internal connection property. The panels produced with the addition of two veneers showed better mechanical properties compared to the other panels in this study. The properties of swelling in thickness, modulus of rupture and modulus of elasticity in perpendicular static bending tests were impaired by the use of blades on the panel faces. The addition of carbon fiber considerably increased the properties of modulus of rupture and modulus of elasticity both in the parallel and perpendicular directions, reaching values 50% higher than the panels without carbon fiber, however, it did not influence the bonding properties internal and screw pullout.